An Investigation into The Linguistic Features of English and Vietnamese Riddles - Đặng Thị Thủy (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The study focuses on finding out the phonetic and lexical features of riddles in English and Vietnamese for the purpose of implication in deducing or finding out the answers for the question as well as teaching and learning English. The data for the study is collected from English and Vietnamese riddles. All examples are selectively collected from English and Vietnamese newspapers, famous books and valid websites, related materials, etc. The study is carried out through the adoption of descriptive, analytic, qualitative, quantitative, and contrastive approaches. In respect of the finding and discussion, we refer to the viewpoints of linguistic features by Maranda, E. (1971) and Pepicello and Green (1982) to describe, analyze and find out similarities and the differences between phonetic and lexical features of riddles in English and Vietnamese in terms of stylistic devices. The quantitative results of occurrence frequencies of phonetic and lexical features of riddles in English and Vietnamese have been taken into careful consideration. We have simultaneously discussed and found the result in both qualitative and quantitative research to enhance the reliability and validity of the study. Hopefully, the findings of the research will provide some useful knowledge of linguistic features in English and Vietnamese riddles as a means of predicting or finding the answers to English and Vietnamese riddles.